Измеритель характеристик излучения мощных светодиодов - Маковская, Е. Г.; Бондаренко, И. Н. (ХНУРЕ, 2017)
In this work construction of optical unit for spectrophotometer LR1 for measurements of LED radiation characteristics in real exploitation conditions proposed. Development construction make it possible to control the radiation spectrum and investigate the spectral sensitivity of photodetector with sizes less then 2×2 cm at spectral range 400..700 nm.
Keywords: Измеритель характеристик излучения; Мощные светодиоды